Variation in Double Object Formation with Dative Verbs: English vs. Korean - Myung-Kwan Park (영어학, 2021)
There has been a multitude of analyses for double object (DO) formation with English dative verbs, which is known to be very productive though constrained by several factors. By contrast, DO formation in Korean is confined to only some of the dative verbs in this language. Honing in on the grammatical aspects of variation in DO formation between English and Korean, this paper investigates exactly where the variation at issue stems from. Assuming that dative verbs like give are lexico-semantically decomposed into the two abstract predicates such as CAUSE and HAVE, we propose that there are two types of CAUSE[strong] and CAUSE[weak]: the former in English encodes strong causation, while the latter in Korean encodes weak causation. Crucially, the two types of CAUSE differ in their [S]emantic/[C]ategorial-selection. CAUSE[strong] can select as its complement either the projection headed by the predicate HAVE or the same projection hosting a modal operator. By contrast, CAUSE[weak] can only select the projection headed by the predicate HAVE. Thus, this paper contributes a better understanding of what (lexico-)syntactic property is at work in materializing the cross-linguistic variation in double object formation with dative verbs. KCI Citation Count: 2